Grapevine, esca complex, and environment: the disease triangle - FISCHER, Michael; PEIGHAMI-ASHNAEI, Samira (Phytopathologia Mediterranea, 2019)
This review compiles the available knowledge on the triple impact of host-pathogens-environment in the progress of the esca disease complex of grapevine. The perennial crop grapevine encounters different biotic and abiotic factors responsible for numerous changes at the various growth stages. This review provides increased understanding of the esca disease complex, with emphasis on (1) the nature of esca-associated fungi as endophytes or pathogens in grapevine, (2) the importance of grapevine genotype and age in relation to resistance or susceptibility to the pathogens, (3) the significant effects of climatic changes, especially drought, on pathogen development and symptomatology, and (4) the physio-biochemical changes in the grapevines arising from the biotic and abiotic interactions. Drought often provides conditions favouring disease development in plants. Physiological and biochemical changes in plants play critical roles in this topic. The constantly increasing economic impacts of esca disease in many grape-producing countries, and the broad lack of knowledge so far, require precise studies on the transcriptional responses to biotic and abiotic factors in grapevines, as effects of “climate change” develop. On the viticultural side, improved management of water and adjusted nutrition balance in vineyards may become useful strategies to mitigate the widespread damage caused by grapevine wood pathogens.